2011
DOI: 10.1007/s00068-011-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of timing and oral anticoagulant/antiplatelet therapy on outcomes of patients affected by hip fractures

Abstract: The "discontinue drug, and delay surgery" strategy is not suitable for patients on anticoagulant (warfarin) therapy affected by a hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…The overall complication rate was 22.4% and was therefore compatible to complication rates described in previous studies [14,21]. The inhouse mortality rate was 4% but showed a significant increase for patients on anticoagulants (7.7%) consistent with other studies showing increased mortality for anticoagulants [22] Dettoni et al were able to determine two main factors for increased mortality and complications, namely warfarin and a delay in time to surgery in a large cohort of 875 hip fractures [23]. DOACS were evaluated as a risk for higher mortality and delay to surgery also by a large metaanalysis [24].…”
Section: Discussionsupporting
confidence: 84%
“…The overall complication rate was 22.4% and was therefore compatible to complication rates described in previous studies [14,21]. The inhouse mortality rate was 4% but showed a significant increase for patients on anticoagulants (7.7%) consistent with other studies showing increased mortality for anticoagulants [22] Dettoni et al were able to determine two main factors for increased mortality and complications, namely warfarin and a delay in time to surgery in a large cohort of 875 hip fractures [23]. DOACS were evaluated as a risk for higher mortality and delay to surgery also by a large metaanalysis [24].…”
Section: Discussionsupporting
confidence: 84%
“…Even in our study, warfarinised patients showed higher mortality compared to patients that do not assume any anticoagulant drugs or antiplatelet therapy. In an observational study by Dettoni et al published in 2011 including 875 patients with PFF, they noticed that warfarin therapy and delay in time to surgery were associated with a significantly higher risk for complications and mortality compared to all other patients [27]. Lawrence et al showed an association between warfarin therapy with prolonged time to surgery and an increased 1-year mortality rate in hip fracture patients and they suggested to consider warfarin therapy a “Red flag” in patients with PFF [28].…”
Section: Discussionmentioning
confidence: 99%
“…Lawrence et al in 2016 [ 18 ] showed an association between warfarin therapy with prolonged time to surgery (mean 46 h versus 24 h for the control group), and an increased 1-year mortality rate in hip fracture patients. In an observational study by Dettoni et al in 2011 [ 19 ] including 875 consecutive hip fracture patients they reported that the presence of two critical factors: warfarin therapy and a delay in time to surgery, was associated with a significantly higher risk for complications and mortality compared to all other patients. They concluded that the “discontinue drug and delay surgery” strategy is not suitable for hip fracture patients on warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%